2021
DOI: 10.3389/fpsyg.2021.667326
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Behavior in Small Doses: A Review of Comparative Research in Evaluating Thin Slices for Behavioral Measurement

Abstract: Thin slices are used across a wide array of research domains to observe, measure, and predict human behavior. This article reviews the thin-slice method as a measurement technique and summarizes current comparative thin-slice research regarding the reliability and validity of thin slices to represent behavior or social constructs. We outline decision factors in using thin-slice behavioral coding and detail three avenues of thin-slice comparative research: (1) assessing whether thin slices can adequately approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 104 publications
0
18
0
Order By: Relevance
“…Scientists applied thin slice observation to a wide variety of research topics (Murphy & Hall, 2021). The method has proven valid in capturing dyadic parent/child interactions and characterizing parenting styles (Frost et al, 2020; James et al, 2012).…”
Section: Exemplar 2: Neighborhood Roving Provides Mixed Methods Data ...mentioning
confidence: 99%
“…Scientists applied thin slice observation to a wide variety of research topics (Murphy & Hall, 2021). The method has proven valid in capturing dyadic parent/child interactions and characterizing parenting styles (Frost et al, 2020; James et al, 2012).…”
Section: Exemplar 2: Neighborhood Roving Provides Mixed Methods Data ...mentioning
confidence: 99%
“…However, in collected video clips, they were not always split into a single screen (e.g., appearing on the screen one by one). Thus, the “thin slice” technique was employed for the split-screen, which can represent the entire interaction even with a short, segmented clip (Murphy & Hall, 2021 ; Murphy et al, 2015 ). Since more clips can be included in the analysis, the length of the sliced segment was set to 20 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…The rating approach could save the coder’s time and effort, but it would be still laborious in the frequent human judgments to be made. To overcome the labor-intensive nature of manual coding, researchers have had to resort to focusing on the segmented clip (Murphy & Hall, 2021 ). A previous study demonstrated nonverbal behaviors in a “thin-sliced” segment could represent nonverbal behavior throughout the interaction (Murphy et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of pertinence to the present research and the majority of existing studies in the spontaneous trait inferences domain is the focus on nonverbal cues (Ambady & Rosenthal, 1992). Research attention on nonverbal cues such as gestures and facial expressions has remained high for the last few decades (Breil et al, 2021; Murphy & Hall, 2021). This is likely because compared to verbal cues, nonverbal cues are known to be more difficult to suppress, control, and monitor, and hence an individual’s traits and internal states are believed to “leak” more through nonverbal channels and be relied on more by observers when making interpersonal judgments (DePaulo, 1992; but see Biel et al, 2013, and Hickman et al, 2021, for discussions on the relative importance of verbal cues in the inferences of some traits).…”
Section: Impression Formation From Nonverbal Cuesmentioning
confidence: 99%
“…While there has been a substantial amount of scholarly interest on the effects of nonverbal cues on interpersonal trait judgments, the overwhelming majority of studies have focused on visually salient cues, such as gaze, body language, and facial expressions (Ambady & Rosenthal, 1992; Murphy & Hall, 2021; Murphy et al, 2015; Wang et al, 2021). The current environment, however, calls for more research attention on how interpersonal judgments and impressions could be formed in the absence of visual cues.…”
Section: Impression Formation From Nonverbal Cuesmentioning
confidence: 99%